TRENDS IN SPATIAL-GEOGRAPHICAL DEVELOPMENT OF URBAN AREAS IN SOUTH CENTRAL PLANNING DISTRICT - Michaela Georgieva (Journal of Bio-Based Marketing)
This article focuses on the status and development of urban areas in the South Central Planning Region in terms of their geography and population status. The paper assesses and analyses mainly the agglomeration area between Plovdiv and Pazardzhik with the complementary role of the city of Haskovo. A general assessment is made of the state of the settlements in the South Central Planning Region and the connectivity between the settlements. An assessment is also made from a spatial hunger point of view as the planning area with its main urbanization areas is positioned about the other regions of the country and the role of cities in Southeast Europe. The evaluations and views made show the possibilities of the cities and settlements to form a geo-economic axis between Pazardzhik-Plovdiv-Haskovo, which would have strategic importance for the regional development of the country. Relevant conclusions and recommendations are made for the regional development of the planning area.